Solopos Media Group Branding Strategy Through The Solopos Goes To Campus Program - Nurhayati, Anisa Pratiwi; Zulhazmi, Abraham Zakky (Universitas Islam Negeri Raden Intan Lampung, 2022)
The digital era has caused many fundamental changes in the world of communication. There are big challenges as well as opportunities that must be faced by the conventional mass media industry in order to survive. One of the conventional media that is affected by the flow of digitization is Solopos. As a regional newspaper published in Solo in 1997, Solopos also tries to adapt to technological developments. In its development, to continue to survive in the midst of increasingly fierce competition in the mass media industry, Solopos Media Group carries out branding through organized events. One of the events held by Solopos is Solopos Goes to Campus. This study intends to describe the Solopos Media Group branding strategy through the Solopos Goes to Campus program. This research uses descriptive qualitative method. Data was collected through observation, interviews, and documentation. In order to test the data validation, this research uses source triangulation technique. The theory used is the theory of Sicco Van Gelder's branding strategy (2005). The results showed that the Solopos Media Group in building branding as a conventional mass media that had been transformed into digital media was carried out through the Solopos Goes to Campus activity. Through this activity, Solopos wants to present an image as a mass media that is close to young people so that it can reach this market share.